Pengaruh Literasi Keuangan Syariah dan Sikap Keuangan Terhadap Perilaku Konsumtif Mahasiswa Aktif Program Studi Manajemen Keuangan Syariah - Aisyah, Siti; Nasrifah, Maula; Maulidiyah, Nailin Nikmatul (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study intends to analyze the influence of Syariah financial literacy and financial attitudes on the consumptive behavior of active students of the Sharia Financial Management Study Program. The research method uses an exploratory quantitative approach with samples determined using Cochran's formula and proportionate stratified random sampling technique. Data were collected through questionnaires, then analyzed using multiple linear regression analysis after classical assumption tests. The results of the study showed that Sharia financial literacy and financial attitudes had a significant effect on students' consumptive behavior. These results contributed to strategies for improving financial literacy and controlling consumption behavior, as well as being a cornerstone in the formation of financial education policies based on Sharia values in the campus environment.